1989
DOI: 10.1507/endocrj1954.36.261
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of Inappropriate Luteinizing Hormone Secretion by Bromocriptine in Polycystic Ovary Syndrome with Elevated Serum Dehydroepiandrosterone Sulfate.

Abstract: Ten clomiphene-resistant, normoprolactinemic women with polycystic ovary syndrome (PCOS) were treated by continuous and increasing administration of bromocriptine (Brc), and changes in hormonal profiles as well as therapeutic efficacy were examined. Ovulation was restored in four patients (responders), and two of them became pregnant, whereas the other six patients did not ovulate with Brc alone (non-responders).Endocrine analyses revealed distinct differences between responders and non-responders: 1) pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Though, the prolactin level significantly decreased in CC+Bcrt group, we could not demonstrate any remarkable change in ovulation as well as pregnancy rate. Studies done by Steingold et al, [17] and Takakura et al, [18] showed various changes in hormonal levels. Buvat et al, observed that there is no significant changes in hormonal profile and clinical characteristics after treatment, with the combination of bromocriptine and clomiphene citrate [19].The study done by Mohammad et al, had shown that the only significant long term bromocriptine therapy in clomiphene citrate resistant polycystic ovarian patients was to lower the serum prolactin concentration, which is similar to our study [20].…”
Section: Resultsmentioning
confidence: 92%
“…Though, the prolactin level significantly decreased in CC+Bcrt group, we could not demonstrate any remarkable change in ovulation as well as pregnancy rate. Studies done by Steingold et al, [17] and Takakura et al, [18] showed various changes in hormonal levels. Buvat et al, observed that there is no significant changes in hormonal profile and clinical characteristics after treatment, with the combination of bromocriptine and clomiphene citrate [19].The study done by Mohammad et al, had shown that the only significant long term bromocriptine therapy in clomiphene citrate resistant polycystic ovarian patients was to lower the serum prolactin concentration, which is similar to our study [20].…”
Section: Resultsmentioning
confidence: 92%